Features of the structure of word-formation chains of adjectives with Latin root morpheme in modern Russian - Stryha, Katsiaryna V. (Journal of the Belarusian State University. Philology, 2021)
The analysis of the part of speech and word formation structure of binary and multicomponent word formation chains that are part of word formation nests with the original word – adjective name with the Latin root morpheme is carried out. The most typical models of part of speech of word formation chains for the considered deadjective nests are revealed. It is established that some features of the organization of word formation chains are predetermined by the part of speech and the method of formation of the derivative, which is at the first stage of derivation. It was found out that the longest and most diverse word formation chains are formed with the participation of abstract nouns with the suffix -ism and verbs at the first stage of derivation; complex adjectival derivative in the first stage typically lead to the formation of two-component derivational chains, prefixed to the formation of ternary chains, adverbial derivatives mainly form a binary chain. It is determined that the most characteristic of the multicomponent deadjective chains with nouns for the first stage of derivationare substantive and adjective derivatives, for the chains with verbs at the first stage – derived nouns and verbs; adjectives at the first stage regularly motivate substantive and adverbial derivatives; adverbs can be motivating only for adverbial derivatives.